Relation between texture and high-rate capacitance of oppositely charged microporous carbons from biomass waste in acetonitrile-based supercapacitors. (10th January 2019) - Redondo, Edurne; Ségalini, Julie; Carretero-González, Javier; Goikolea, Eider; Mysyk, Roman
Abstract: A biomass-derived activated carbon with a systematic control over the pore size distribution is used to decode the effect of pore size distribution on charge dynamics in organic acetonitrile-based supercapacitors. Distinct trends in the high-current capacitance of the positive and negative electrodes are revealed by isolating the ion-specific accessible pore width and specific surface area from the total values calculated on the basis of low-temperature nitrogen adsorption/desorption isotherms. A size match between ions and pores for each separate electrode is established to maximize gravimetric capacitance under high current load. Most importantly, the high-current gravimetric capacitance demonstrates the existence of an optimum micropore width depending on polarization as well as no need for wide micropores or mesopores for ensuring rapid capacitive response.